Interiors : - Nielson, Karla J. (McGraw-Hill, 2002)
Interiors: An Introduction offers an introduction to the elements, practice, and aesthetics of residential and nonresidential interior design. The text presents timeless design principles and elements and their application to interiors. In addition, the authors describe the numerous choices of materials, furnishings, and components used in interior design.